2020
DOI: 10.1590/1414-431x20198389
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll treatment combined with photostimulation increases glycolysis and decreases oxidative stress in the liver of type 1 diabetic rats

Abstract: Photodynamic therapy (PDT) promotes cell death, and it has been successfully employed as a treatment resource for neuropathic complications of diabetes mellitus (T1DM) and hepatocellular carcinoma. The liver is the major organ involved in the regulation of energy homeostasis, and in pathological conditions such as T1DM, changes in liver metabolic pathways result in hyperglycemia, which is associated with multiple organic dysfunctions. In this context, it has been suggested that chlorophyll-a and its derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The pioneer works on the inhibition of lipid peroxidation by copper chlorophylls were developed by Sato’s group [ 168 , 188 ]. Later, this effect was reported in numerous tissues, normally through the formation of lipid hydroperoxides [ 183 ], but also through the TBARS method: in lymphocytes in a concentration-dependent manner up to 75% [ 185 ], in kidney and heart tissues at the same level as ascorbic acid [ 189 ], and in the liver [ 190 , 191 , 192 ], brain [ 187 ], and serum [ 182 ].…”
Section: Antioxidant Capacity Of Chlorophyllsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pioneer works on the inhibition of lipid peroxidation by copper chlorophylls were developed by Sato’s group [ 168 , 188 ]. Later, this effect was reported in numerous tissues, normally through the formation of lipid hydroperoxides [ 183 ], but also through the TBARS method: in lymphocytes in a concentration-dependent manner up to 75% [ 185 ], in kidney and heart tissues at the same level as ascorbic acid [ 189 ], and in the liver [ 190 , 191 , 192 ], brain [ 187 ], and serum [ 182 ].…”
Section: Antioxidant Capacity Of Chlorophyllsmentioning
confidence: 99%
“…Finally, the main biomarker of oxidative stress in proteins is the formation of carbonyl (CO) groups (aldehydes and ketones), especially on Pro, Arg, Lys, and Thr residues [ 197 ]. Measuring this oxidative biomarker, copper chlorophyllin has shown its ability to decrease the level of protein carbonyls in kidney and heart tissues at rates similar to those of ascorbic acid [ 190 ] in liver tissues [ 184 , 188 , 192 ]. An even more marked effect was observed when Caenorhabditis elegans consumed a pheophorbide-rich diet, reducing the carbonyl groups up to 80% in comparison with a control group [ 198 ].…”
Section: Antioxidant Capacity Of Chlorophyllsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorophyll is an abundant green pigment and non-nutrient compound ubiquitously found in higher plants and other photosynthetic organisms. Chlorophyll has been widely used to prevent various chronic diseases because of its numerous pharmacological effects, such as anti-cancer, anti-inflammatory, and antioxidant properties (170)(171)(172). Recently, more and more studies have reported that chlorophyll also plays important roles in ameliorating obesity.…”
Section: Chlorophyllmentioning
confidence: 99%
“…vulgaris was possible to aggregate in the tumor site and produce oxygen under the laser irradiation condition to promote the radiation responses of the tumor. In addition, C. vulgaris contains abundant chlorophyll, a natural photosensitizer that can release reactive oxygen species (ROS) to kill the tumor cells when irradiated with laser for photodynamic therapy (PDT). …”
Section: Introductionmentioning
confidence: 99%